Baculovirus Expression Vectors that Incorporate the Foreign Protein into Viral Occlusion Bodies. (January 2003) - Je, Y.H.; Jin, B.R.; Park, H.W.; Roh, J.Y.; Chang, J.H.; Seo, S.J.; Olszewski, J.A.; O'Reilly, D.R.; Kang, S.K.
Current baculovirus expression systems typically produce soluble proteins that accumulate within the infected insect cell or are secreted into the growth medium. A system has now been developed for the incorporation of foreign proteins, along with the matrix protein, polyhedrin, into baculovirus occlusion bodies. Initial studies showed that a recombinant virus expressing a translational fusion between polyhedrin and GFP did not form occlusion bodies. However, a baculovirus coexpressing native polyhedrin and the polyhedrin-GFP fusion protein formed occlusion bodies that fluoresced under UV light, demonstrating that they included the polyhedrin-GFP fusion protein. This was confirmed by immunoblot analysis. Thus, incorporation of a foreign protein into occlusion bodies depends on an interaction between native polyhedrin and the polyhedrin fusion protein. Electron microscopy demonstrated that the occlusion bodies containing GFP also incorporated virions as expected. These ColorPol occlusion bodies were as infectious to insect larvae as occlusion bodies produced by wild-type virus. This new system expands the capabilities for foreign gene expression by baculoviruses, which has implications for biopesticide design, novel vaccine delivery systems, and fusion protein purification applications.